The association of outdoor temperature with blood pressure, and its influence on future cardio-cerebrovascular disease risk in cold areas - Yu, B; Jin, S; Wang, C; Yan, S; Zhou, X; Cui, X; Tang, Z; Luan, Q; Guo, Y; Bian, Z; Li, L; Zhengming Chen; et al. (Lippincott, Williams and Wilkins, 2020)
OBJECTIVES: To explore whether lower outdoor temperature increases cardio-cerebrovascular disease risk through regulating blood pressure and whether indoor heating in winter is beneficial to prevent cardio-cerebrovascular disease in cold areas.